Compulsory jurisdiction of the International Court of Justice : a myth? : a statitstical analysis of contentious cases - Oda, Shigeru (2000)
Examines the manner in which certain contentious cases presented to the International Court of Justice have disappeared from view and of whether a judgement, once handed, has actually been complied with by the parties to the dispute.